Wood Culture in Ancient India as Reflected from Identification of Confiscated Wooden Artifacts Dating between 14-19th Century A.D. - Gupta, Sangeeta; Rana, K. S. (Indian Forester, 2013)
Confiscated wooden artifacts in the form of sculpture, boxes, beds belonging to 14 -19 centuries were studied for their wood type. Based on very small wood chips taken out from the artifacts, the wood identification was carried out. The artifacts were found to be made up of Juniperus species, Madhuca longifolia (Mahua), Tectona grandis (Teak), Pterocarpus marsupium (Bijasal), Ficus species and Acacia species. All these woods except for Ficus are well known woods famous for their durability and strength. The choice of species of these woods for furniture and sculpture is indicative of good knowledge of wood properties during those times.